Comparison of irrigant activation devices and conventional needle irrigation on smear layer and debris removal in curved canals. (Smear layer removal from irrigant activation using SEM). (8th March 2021) - Andreani, Yasmina; Gad, Benjamin Thomas; Cocks, Thomas Charles; Harrison, Jonathan; Keresztes, Mark Edward; Pomfret, James Kennan; Rees, Evan Benjamin; Ma, Duoduo; Baloun, Brett Lindsay; Rahimi, Mehdi
Abstract: Aim: To compare the effectiveness of smear layer and debris removal in the final rinse of curved canals of permanent molars using different commercially available irrigant activation devices. Methods: The mesial roots of 74 extracted maxillary and mandibular molars were instrumented using the Mtwo nickel–titanium rotary system (VDW GmbH, Munich, Germany). They were then randomly assigned to one of three groups, varying in their final rinse protocol. Group 1 ( n  = 15) – conventional needle irrigation with 4% NaOCl; Group 2 ( n  = 19) – EndoActivator® (Dentsply Tulsa Dental Specialties, Tulsa, OK, USA) with 4% NaOCl; Group 3 ( n  = 17) – XP‐endo® Finisher (FKG Dentaire SA, La Chaux‐de‐Fonds, Switzerland) with 4% NaOCl. After the final rinse, all canals were flushed with 1 mL 15% EDTA for 60 s and then flushed with saline. The roots were split longitudinally and prepared for scanning electron microscope imaging. ImageJ for Windows was utilised to assess the images for smear layer removal, while two blinded investigators assessed debris presence in the middle and apical thirds using a 5‐point scale. Results: There was no significant difference in smear layer and debris removal between treatment and control groups in the same canal zones. A significant difference was noted across different canal zones both within and across the groups. Conclusion: There is no statistically significant difference in effectiveness between activated irrigation techniques and manual activation. Further investigations are required to evaluate all methods available and determine the most efficient technique to irrigate successfully.